A 7-year retrospective study of biopsied oral lesions in 460 Iranian patients - Shila Ghasemi Moridani; Fatemeh Shaahsavari; Mohammad Bagher Adeli (Revista Sul-Brasileira de Odontologia, 2015)
Frequency of oral lesions is varied in different population and knowledge of diseases prevalence in a geographic location will improve preventive measures. Objective: The objective of this study was to determine the prevalence of oral biopsied lesions in a major oral pathology laboratory center of city of Tehran. Material and methods: A retrospective study was done on data obtained from the archive of oral and maxillofacial pathology department of Islamic Azad University, dental branch of Tehran, from 2005 to 2011. Following variables were analyzed: age, gender, anatomic location, and the histological results obtained. Lesions were classified to 18 different categories. Data were analyzed using the SPSS version 12.0 for windows Xp. All the data were recorded in Microsoft Office Excel for further evaluation and making a data bank to easy access. Results: Of the 460 patients studied, the mean age was 38 years. The most frequent lesions were in the group of reactive lesions (22.51%), followed by odontogenic cysts. The most frequent lesion was radicular cyst and odontogenic keratocyst (keratocystic odontogenic tumor). Malignant lesions constituted 2.38%, of which squamous cell carcinoma was the most common malignancy (1.52%). Mandible was the most common location for occurrence of lesions (32.6%) followed by gingiva (11.95%). Conclusion: Our study provides helpful information of oral lesion’s distribution in an Iranian population. The results showed high frequency of odontogenic keratocyst (keratocystic odontogenic tumor) which is not in agreement with other studies and need more evaluation of etiological factors.